2018
DOI: 10.1186/s13046-018-0900-6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ultrasound exposure on P-glycoprotein-mediated multidrug resistance in vitro and in vivo

Abstract: BackgroundMultidrug resistance (MDR) is often responsible for the failure of chemotherapy treatment, and current strategies for cancer MDR are not adequately satisfying as to their efficacy and safety. In this study, we sought to determine the anti-MDR effects of ultrasound (US) irradiation and its underlying mechanisms against drug-resistance.MethodsMDR variant MCF-7/ADR cell lines and endothelial cell lines were used to determine the appropriate ultrasound intensity for in vitro experiments. MCF-7/ADR cell a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 55 publications
(53 reference statements)
0
12
0
Order By: Relevance
“…Focused US has been used recently to target DNA-loaded microbubbles located within tumor’s neovasculature to facilitate release of genetic material locally into the tumor [35, 36]. In particular, US has been noted causing the process of sonoporation thus producing transient pores in the cancer cell membranes through which molecules are able to enter the cell [20, 37, 38]. Of interest, successful delivery of genetic material by using microbubbles induces apoptosis in cancer cells and reduces tumor growth [39, 40].…”
Section: Discussionmentioning
confidence: 99%
“…Focused US has been used recently to target DNA-loaded microbubbles located within tumor’s neovasculature to facilitate release of genetic material locally into the tumor [35, 36]. In particular, US has been noted causing the process of sonoporation thus producing transient pores in the cancer cell membranes through which molecules are able to enter the cell [20, 37, 38]. Of interest, successful delivery of genetic material by using microbubbles induces apoptosis in cancer cells and reduces tumor growth [39, 40].…”
Section: Discussionmentioning
confidence: 99%
“…Then, the cells were fixed with 4% polyoxymethylene, permeabilized with 0.2% Triton X-100 and blocked with PBS containing 5% bovine serum albumin. The immunofluorescence analysis was performed as described previously 30, 31. The primary antibody details are available in Table S6.…”
Section: Methodsmentioning
confidence: 99%
“…This up-regulating trend in KB/VIN diminished the functional inhibitory potency of caffeic acid, resulting in weaker MDR reversing effects. Previous research has revealed that the oxidative stress might have a role in the regulation of P-gp expression [43]. As caffeic acid exhibited significant ROS-related anti-oxidant effects, the influence of caffeic acid on ROS production in KB/VIN cell line was performed.…”
Section: Discussionmentioning
confidence: 99%